Diet quality and its contributing factors among adults in three districts of Selangor, Malaysia - Pondor, Ibnteesam (2017)
Food price forms a major part of the food environment and is an important influence on food choices. Research on daily dietary cost(DDC)and diet quality (DQ) has been hindered by a lack of data in Malaysia. This cross-sectional study aimed to examine associations between socio-economic characteristics, dietary intake, BMI and DDC with DQ among adults in Selangor. A total of 450 adults were recruited from housing areas in Bangi, Selayang and Bandar Petaling Jaya. Recruitment involved one adult from odd-numbered houses in selected streets who voluntarily participated. Socio-economic characteristics and anthropometric measurements were obtained during face-to-face interviews. Dietary data was collected using a validated Food Frequency Questionnaire and Nutritionist ProTM software was used to analyze nutrient intakes, thus evaluating DQ using a Healthy Eating Index (HEI). DDC (RM/ 2000Kcal) was calculated using food prices from the Ministry of Trade, Cooperatives and Consumerism. SPSS version 22.0 was used for all statistical analyses. There were 35.8% of males and 64.2% of females. Majority of them were working adults (66.0%) with mean age 37.55± 11.0, had at least secondary school education (97.2%) and reported median personal income of RM3000 (2400) and household income of RM4000 (3000) and a majority of them (59.3%)lived in low cost housing. Respondents with normal BMI counted 38.9% while 22.0% were obese and 36.7% were overweight. There was 50.6% (N= 228) of respondents with energy misreporting and therefore analysis was carried out for both total respondents and plausible reporters. The mean HEI score of plausible reporters (N= 222) was 60.96 ±10.22. Respondents achieved more than 55% of the Malaysian Dietary Guidelines for most HEI components except for milk products (46.8%) and total sodium (12.4%). There were no statistically significant difference (p> 0.05) between HEI scores and socio-economic characteristics except for age groups (p= 0.041) for total respondents and personal income (p= 0.029) for plausible reporters. There was also no significant difference in mean HEI scores with regards to BMI (p> 0.05). There were significant weak positive correlations between energy adjusted carbohydrate (r= 0.189, p= 0.009) and protein (r= 0.141, p= 0.014) and HEI scores (N= 222). The median crude DDC was RM16.73 (12.50) while energy adjusted DDC was RM10.81 (4.45)/ 2000kcal for plausible reporters. The highest contributors to total DDC were cereal products (20.1%), non-alcoholic beverages (18.0%) and confectionaries (13.4%). The multiple linear regression model concluded that energy adjusted fat (β= -0.183) and DDC (β= 0.244) were significant contributors to diet quality (N= 222; p= 0.013). Results from this study suggests that higher diet quality was more expensive than less healthy choice. It not only serves as a stepping stone for more research into examining DDC and DQ in a Malaysian setting but also as a basis for policy makers in gearing subsidies towards more healthful food choices. This study comes at a timely moment especially when there is a need for everybody especially those of low socio-economic background to get access to healthy foods so as to improve health and prevent non-communicable diseases.